Dementia caregiver burden: reliability of the Brazilian version of the Zarit caregiver burden interview - Taub,Anita (2004)
The object of this article is to examine the reliability of the Brazilian version of the Zarit Caregiver Burden Interview (ZBI). The instrument is a 22-item scale assessing the extent to which caregivers view their responsibilities as having an adverse impact on their social life, health, emotional well-being, and finances. We assessed 50 primary informal caregivers of demented patients coming from 3 different health care centers, using the test-retest method. Analysis of the results showed an intraclass reliability coefficient of 0.88, while Cronbach's coefficient alpha was 0.77 for the test and 0.80 for the retest items. The Brazilian version of ZBI shows sufficient reliability, comparable to the original version.